Novel Amine Terminated Elastomeric Oligomers and Their Effects on Properties of Epoxy Resins as a Toughener - (:unkn) unknown (WILEY-BLACKWELL, 2010)
The objective of this study was to investigate the effects of amine terminated elastomeric epoxy tougheners on the mechanical and thermal properties of diglycidyl ether of bisphenol A based epoxy resin. The amine terminated polycaprolactone (PCL) (1) and PCL-PDMS-PCL (2) based oligomers were synthesized and characterized by FTIR spectroscopy. The stoichiometrical amount of the reactive oligomers as toughener, reactive epoxy resin and the curing agent, 4,4'-diaminodiphenyl sulfone (DIDS) were mixed and degassed. The homogenous mixtures were cured at 120 degrees C into the preheated molds. The mechanical and thermal characterizations of toughened epoxy resin system were evaluated. It has been shown that the mechanical and thermal properties of toughened epoxy system vary as a function of the chemical structure and the concentration of rective oligomers. Higher mechanical properties were obtained for epoxy resin toughened by PCL-PDMS-PCL (2) based oligomer. (C) 2009 Wiley Periodicals, Inc. J Appl Polym Sci 115: 37-45, 2010
Keywords: oligomers; toughness; curing of polymers; thermosets; mechanical properties; PHASE-SEPARATION; STOICHIOMETRY; KINETICS; CURE